2021
DOI: 10.3389/fimmu.2021.813331
|View full text |Cite
|
Sign up to set email alerts
|

A Combination of Biomarkers Predict Response to Immune Checkpoint Blockade Therapy in Non-Small Cell Lung Cancer

Abstract: Immune checkpoint blockade (ICB) therapy has provided clinical benefits for patients with advanced non-small-cell lung cancer (NSCLC), but the majority still do not respond. Although a few biomarkers of ICB treatment response have been developed, the predictive power of these biomarkers showed substantial variation across datasets. Therefore, predicting response to ICB therapy remains a challenge. Here, we provided a concise combinatorial strategy for predicting ICB therapy response and constructed the ICB tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…Recent advances in ICBs therapy like targeting programmed cell death protein 1 (PD-1) / PD-ligand 1 (PD-L1) and cytotoxic T-lymphocyte-associated protein 4 (CTLA-4) has provided clinical bene ts for patients with lung cancer, but the majority still do not respond. Although a few biomarkers of ICB treatment response have been developed, the predictive power of these biomarkers showed substantial variation across datasets 28,29 . To evaluate immunotherapy predictive value of TTYH3, we utilized the TIDE web tool, which is a computational framework developed to evaluate potential of tumor immune escape based on the gene expression pro les of cancer samples.…”
Section: Ttyh3 Owned a Predictive Value For Immunotherapy Response In...mentioning
confidence: 99%
“…Recent advances in ICBs therapy like targeting programmed cell death protein 1 (PD-1) / PD-ligand 1 (PD-L1) and cytotoxic T-lymphocyte-associated protein 4 (CTLA-4) has provided clinical bene ts for patients with lung cancer, but the majority still do not respond. Although a few biomarkers of ICB treatment response have been developed, the predictive power of these biomarkers showed substantial variation across datasets 28,29 . To evaluate immunotherapy predictive value of TTYH3, we utilized the TIDE web tool, which is a computational framework developed to evaluate potential of tumor immune escape based on the gene expression pro les of cancer samples.…”
Section: Ttyh3 Owned a Predictive Value For Immunotherapy Response In...mentioning
confidence: 99%
“…However, in other studies these have also been shown to be of weak predictive value (5). Recently proposed cancer immune predictor suggests using a combination of biomarkers to better predict the response of ICB (6,7). The neoepitope load is based on predicted neoepitopes, however, with only 2-4% of these epitopes giving a T cell response, studies have tried to explore for more precise prediction strategies (8) or to validate the presence of truly immunogenic neoepitopes as a more well-suited immune predictor (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…Immune checkpoint blockade (ICB) therapy has revolutionized the treatment of advanced NSCLC. It has improved the overall survival of NSCLC patients, but only a few patients have benefited in the clinical setting ( Jiang et al, 2021 ). The objective response rate to PD-1 blockade (Pembrolizumab) is 19.4% for all the patients with a median overall survival of 12.0 months ( Garon et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%